2011
DOI: 10.1177/0959683611427337
|View full text |Cite
|
Sign up to set email alerts
|

Lake-level changes and fire history at Lagunillo del Tejo (Spain) during the last millennium: Climate or humans?

Abstract: Hydroclimatic variability is expected to be affected by global warming in the Mediterranean region where climate, fire and human activities are known to be interdependent. The latter is examined here for the past millennium by studying paleoenvironmental indicators from a sedimentary sequence at Lagunillo del Tejo (Cuenca, central Spain). Inferred changes in fire activity and lake levels are based on records of macrocharcoals and plant/algal macrofossils, respectively, and are compared with independent informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 43 publications
(53 reference statements)
2
44
0
5
Order By: Relevance
“…De un modo similar, tanto en la cercana laguna de La Cruz como en el Lagunillo del Tejo se reconstruye un clima más húmedo para la PEH. Así, en La Cruz (Julià et al, 1998;RomeroViana, 2010) también se ha descrito la sedimentación de facies laminadas, procesos meromícticos y alto nivel de agua, mientras en el Lagunillo del Tejo (López-Blanco et al, 2011) se reconstruyen niveles del lago más altos durante esta etapa. El desarrollo de las condiciones meromícticas en estos lagos podría estar relacionado con factores climáticos (mayor precipitación, temperaturas más frías y niveles más altos de los lagos), antrópicos, como la expansión de la mesta (trashumancia) en la zona, facilitando los aportes detríticos de finos por roturación y quema de tierras para pastos, y el aumento de la bioproductividad en los lagos (Julià et al, 1998).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…De un modo similar, tanto en la cercana laguna de La Cruz como en el Lagunillo del Tejo se reconstruye un clima más húmedo para la PEH. Así, en La Cruz (Julià et al, 1998;RomeroViana, 2010) también se ha descrito la sedimentación de facies laminadas, procesos meromícticos y alto nivel de agua, mientras en el Lagunillo del Tejo (López-Blanco et al, 2011) se reconstruyen niveles del lago más altos durante esta etapa. El desarrollo de las condiciones meromícticas en estos lagos podría estar relacionado con factores climáticos (mayor precipitación, temperaturas más frías y niveles más altos de los lagos), antrópicos, como la expansión de la mesta (trashumancia) en la zona, facilitando los aportes detríticos de finos por roturación y quema de tierras para pastos, y el aumento de la bioproductividad en los lagos (Julià et al, 1998).…”
Section: Discussionunclassified
“…Esta fase de mayor erosión correspondería con la de mayor impacto humano en la cuenca e incluiría incendios durante las Guerras Carlistas y cambios de usos del suelo tras la Desamortización al propiciar el parcelamiento agrícola, el aumento en la población de Cañada del Hoyo y la construcción de terrazas agrí-colas en la zona de lagos (López-Blanco et al, 2011). Aunque la sedimentación de limos más finos sugiere una recuperación de los niveles hidrológicos durante el siglo XIX, los elevados valores de la relación TOC/TN testifican el elevado impacto humano en la cuenca hasta mediados del siglo XX.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…It peaked ca. 600 AD ( Figure 6) and decreased afterwards suggesting a reduction of soil erosion, coherent with lower human pressure after the Visigoth decline (last half of 7 th century AD) and during the Moorish period (8 th -11 th century AD) (Burjachs, 1996;López-Blanco et al, 2011). Fe and Ti profiles track the fining upward sequences and demonstrate the significant alluvial influence in the lake sedimentation during Unit V when diatom abundance is the lowest in the sequence maybe due to a dilution effect caused by the high clastic sediment input.…”
Section: Depositional Evolution Of La Parramentioning
confidence: 91%
“…In the Iberian Peninsula, numerous Late Holocene lake sequences have been analysed in a variety of geographic, climatic and ecologic settings ( Julià et al, 1998;Luque & Julià, 2002;Pla & Catalan, 2005;Moreno et al, 2008Moreno et al, , 2009Martín-Puertas et al, 2009;López-Merino et al, 2011;Morellón et al, 2011;Corella et al, 2012;Currás et al, 2012;Höbig et al, 2012)using a variety of geological (facies, geochemistry) and biological (pollen, ostracods, diatoms, quironomids) proxies Martín-Puertas et al, 2009;Morellón et al, 2011;Corella et al, 2012;Currás et al, 2012;Höbig et al, 2012). Diatom studies have demonstrated large environmental changes in Iberian lakes during the last 2000 years in water depth, salinity and trophic status: Laguna de Medina (Reed et al, 2001), Sanabria (Luque and Julià, 2002), Enol ( López-Merino et al, 2011), La Cruz (Julià et al, 1998;Kiss et al, 2007), Arreo , Montcortès (Scussolini et al, 2011), Estanya (Riera et al, 2004), Estany Redon (Plá and Catalán, 2005), Zoñar and Lagoa Grande (Reed, 1998;Leira, 2005). The available records show that Iberian lake dynamics responded primarily to changes in hydrology, with relatively humid conditions coinciding with the Iberian-Roman Period (IRHP, 650 BC-350 AD;, early Middle Ages (Dark Ages, DA, 500-900 AD; Moreno et al, 2012) and the LIA (1300-1850 AD; Morellón et al, 2011).…”
Section: Introductionmentioning
confidence: 99%